2022
DOI: 10.1096/fj.202200488r
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from mesenchymal stem cells attenuate diabetic kidney disease by inhibiting cell apoptosis and epithelial‐to‐mesenchymal transition via miR‐424‐5p

Abstract: Diabetic kidney disease (DKD) is well-acknowledged as one of the most common complications in diabetes mellitus. Recent studies have demonstrated the promising role of mesenchymal stem cell-derived exosomes (MSC-exos) as a cell-free treatment strategy for DKD. The present study sought to investigate the therapeutic potential and the underlying mechanisms of MSC-exos in DKD. The authentication of MSC-exos was validated by western blot, transmission electron microscope (TEM), and nanosight tracking analysis (NTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…30 Similarly, Cui et al found that exosomes derived from MSCs attenuate DKD by inhibiting cell apoptosis and epithelialto-mesenchymal transition via miR-424-5p. 31 These results indicate that MSC-derived exosomes may be a promising therapeutic cell-free strategy for DKD. Additionally, the latest study showed that MSCs protect kidney injury in diabetic rats through an autophagy-mediated antisenescent mechanism.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…30 Similarly, Cui et al found that exosomes derived from MSCs attenuate DKD by inhibiting cell apoptosis and epithelialto-mesenchymal transition via miR-424-5p. 31 These results indicate that MSC-derived exosomes may be a promising therapeutic cell-free strategy for DKD. Additionally, the latest study showed that MSCs protect kidney injury in diabetic rats through an autophagy-mediated antisenescent mechanism.…”
Section: Discussionmentioning
confidence: 82%
“…Wang et al reported that MSC‐derived exosomes transferring miR‐22‐3p ameliorate DKD through the NLRP3 signalling pathway 30 . Similarly, Cui et al found that exosomes derived from MSCs attenuate DKD by inhibiting cell apoptosis and epithelial‐to‐mesenchymal transition via miR‐424‐5p 31 . These results indicate that MSC‐derived exosomes may be a promising therapeutic cell‐free strategy for DKD.…”
Section: Discussionmentioning
confidence: 93%
“…Alasmari et al 77 illustrated that exosomes derived from BMMSCs impeded the progression of CKD by interfering with fibrosis and apoptosis. Moreover, MSCs-Exo exhibited anti-apoptotic effect on KD progression by transferring miRNAs (eg, miR-199a-3p 44 and miR-424-5p 81 ). What’s more, exosomes released from MSCs preconditioned with melatonin blocked apoptosis by decreasing the levels of caspase-3 67 , which had a protective effect against CKD.…”
Section: Efficacy and Mechanisms Of Mscs Therapy In Kdmentioning
confidence: 99%
“…55 The study revealed that miR-133b reduced TGFβ1-induced EMT of HK2 cells and renal interstitial fibrosis in aged mice with UUO. 57 In addition, MSC-EVs also suppress EMT via several other pathways. Cui et al observed that MSC-EVs decreased renal cell apoptosis and inhibited EMT in diabetic kidneys in diabetes/diabetes mice.…”
Section: Suppressing Emtmentioning
confidence: 99%